2021
DOI: 10.3390/ma14247767
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitated Particle Refinement in High-Cr ODS Steels by Microalloying Element Addition

Abstract: Two oxide-dispersion-strengthened (ODS) steels with different compositions (14Cr-ODS and 14Cr-Zr-ODS) were investigated to reveal the influences of microalloying element addition on the microstructure and to clarify the refining mechanism of precipitated particles. TEM and HRTEM results indicated that precipitated particles in the Zr-containing ODS steel had finer sizes and dispersed more homogeneously within the grains. It was found that rhombohedral Y4Zr3O12 particles with complex lattice structures were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Wu et al [ 39 ] showed that the UTS of Fe–15Cr–2W–0.35Ti–0.6Y 4 Zr 3 O 12 ODS steel, produced by HIP, was 1006 MPa, with a UE of 15.5% at RT. Li et al [ 79 ] indicated that the UTS of Fe–14Cr–1.5W–0.9Zr–0.45Y 2 O 3 ODS steel, prepared by HIP, was 981 MPa, with a UE of 16.7% at RT. Li et al [ 80 ] reported that the UTS of Fe–14Cr–2W–0.3Ti–0.3Y 2 O 3 ODS steel, fabricated by SPS, was ~940 MPa to ~1500 MPa at RT, with sintering temperatures ranging from 950 °C to 1025 °C, and it should be noted that the UTS decreased with the increase in the sintering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [ 39 ] showed that the UTS of Fe–15Cr–2W–0.35Ti–0.6Y 4 Zr 3 O 12 ODS steel, produced by HIP, was 1006 MPa, with a UE of 15.5% at RT. Li et al [ 79 ] indicated that the UTS of Fe–14Cr–1.5W–0.9Zr–0.45Y 2 O 3 ODS steel, prepared by HIP, was 981 MPa, with a UE of 16.7% at RT. Li et al [ 80 ] reported that the UTS of Fe–14Cr–2W–0.3Ti–0.3Y 2 O 3 ODS steel, fabricated by SPS, was ~940 MPa to ~1500 MPa at RT, with sintering temperatures ranging from 950 °C to 1025 °C, and it should be noted that the UTS decreased with the increase in the sintering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…ODS steel is strengthened by dispersing oxide particles, which strongly impede dislocation motion and thereby increase the onset stress of plastic deformation and creep resistance [ 2 , 3 ]. ODS ferritic/martensitic steels containing 9–12 mass% Cr have been developed as fuel cladding material because of their high creep strength at elevated temperatures and adequate resistance to neutron irradiation embrittlement [ 4 , 5 , 6 , 7 , 8 , 9 ]. The performance of ODS steel largely depends on the particle size and stability of the dispersed oxide nanoparticles [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%